2004
DOI: 10.1159/000082317
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Postoperative Enterocutaneous Fistulas by High-Pressure Vacuum with a Normal Oral Diet

Abstract: Background/Aims: Enterocutaneous fistulas are associated with prolonged hospital stay, high morbidity/mortality, and increased hospital costs. This study aims to describe the use of a vacuum system and normal oral diet in dealing with this problem. Methods: Seventy-four consecutive patients with recent and defined external postoperative fistulas were analyzed. Abdominal imaging was used to exclude abscess and distal obstruction. The fistula tract was sealed with Foley catheter, connected to a negative pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…Since that time, others have corroborated our findings through a case report, 7 a small case series, 8 and a larger case series that suggested that negative-pressure dressing may improve outcomes over standard conservative therapy in patients with ECFs. 9 Throughout the 1980s and early 1990s, there was much interest in the potential for somatostatin agonists, such as octreotide, to increase closure rates in patients with ECFs. Despite many studies suggesting that these agents did improve outcomes, a general consensus was reached that they provided only a modest benefit over traditional conservative therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since that time, others have corroborated our findings through a case report, 7 a small case series, 8 and a larger case series that suggested that negative-pressure dressing may improve outcomes over standard conservative therapy in patients with ECFs. 9 Throughout the 1980s and early 1990s, there was much interest in the potential for somatostatin agonists, such as octreotide, to increase closure rates in patients with ECFs. Despite many studies suggesting that these agents did improve outcomes, a general consensus was reached that they provided only a modest benefit over traditional conservative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] The purpose of this report is to examine the factors associated with successful closure of ECFs treated with negative-pressure dressings. Our closure rate is then compared with rates reported in the literature with standard conservative management.…”
mentioning
confidence: 99%
“…This has the potential advantage of preserving small bowel secretions, although it is unacceptable to many patients. Another technique that has been used to facilitate enteral feeding is vacuum sealing of the fistula tract86–88. This has been described in a series of 74 patients with postoperative enterocutaneous fistula who were fed orally; a high rate of spontaneous fistula closure was reported87.…”
Section: Nutritional Supportmentioning
confidence: 99%
“…On the other hand, use of NPWT in the OA has been reported in several case reports and case series with good or even excellent results. Authors have concluded that NPWT has been safe and has not been associated with a high incidence of enteric fistulae . Several novel methods and devices have been developed to improve the treatment provided to patients with OA.…”
Section: Management Of Eafmentioning
confidence: 99%